1992
DOI: 10.1111/j.1365-3083.1992.tb03092.x
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Immunological Properties of the Protein Fraction of A36, a Major Antigen Complex of Mycobacterium paratuberculosis

Abstract: TMA (thermostable macromolecular antigens) are major mycobacterial complexes present in all mycobacteria. We have purified A36, the TMA complex of M. paratuberculosis, the etiological agent of paratuberculosis (Johne's disease), and shown by the immune electron microscopy approach its presentation at the cell surface. The immunodominance of the A36 complex in Johne's disease was suggested by comparative ELISA analysis of infected bovine sera, using either A36 or M. paratuberculosis total soluble sonicate as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
51
1
2

Year Published

1992
1992
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 28 publications
4
51
1
2
Order By: Relevance
“…Mycobacterium paratuberculosis, the etiological agent of Johne's disease, contains a major antigen complex called A36 which is highly recognized by sera from cattle infected with M. paratuberculosis (6,9). We have recently shown that a 34-kDa protein of the A36 complex is immunodominant and contains B epitopes specific for all tested mycobacteria, including Mycobacterium bovis and Mycobacterium avium (6).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Mycobacterium paratuberculosis, the etiological agent of Johne's disease, contains a major antigen complex called A36 which is highly recognized by sera from cattle infected with M. paratuberculosis (6,9). We have recently shown that a 34-kDa protein of the A36 complex is immunodominant and contains B epitopes specific for all tested mycobacteria, including Mycobacterium bovis and Mycobacterium avium (6).…”
mentioning
confidence: 99%
“…The 897-bp open reading frame coded for a novel protein containing specific B epitopes. The occurrence of well-defined hydrophobic and hydrophilic portions suggests the wall location of the protein.Mycobacterium paratuberculosis, the etiological agent of Johne's disease, contains a major antigen complex called A36 which is highly recognized by sera from cattle infected with M. paratuberculosis (6,9). We (18), and the insert (boxed in Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…paratuberculosis possesses a complex cell-wall containing several immunogenic proteins, glycopeptides and glycolipids such as lipoarabinomannan, shared with other mycobacterial species [11,12]. Amongst the protein antigens, protein p34 was identified as immunodominant for bovine B cells [13]. The hydrophilicity profile of p34 identified two distinct regions: a strongly hydrophobic aminoterminal region composed of aminoacids 40-160 and a highly hydrophilic domain corresponding to residues 161-298.…”
Section: Introductionmentioning
confidence: 99%